Resting Heart Rate and Long-Term Outcomes in Patients with Percutaneous Coronary Intervention: Results from a 10-Year Follow-Up of the CORFCHD-PCI Study - Ying-Ying Zheng; Ting-Ting Wu; You Chen; Xian-Geng Hou; Yi Yang; Xiang Ma; Yi-Tong Ma; Jin-Ying Zhang; Xiang Xie (Cardiology Research and Practice)
Background. The relationship between heart rate in CAD patients who underwent percutaneous coronary intervention (PCI) and had long-term outcomes over up to 10 years of follow-up has not been investigated. Methods. All patients were from the CORFCHD-PCI, a retrospective cohort study that included a total of 6050 CAD patients who underwent PCI from January 2008 to December 2016. One patient was excluded due to a lack of heart rate data. Ultimately, 6049 patients were enrolled. The primary outcome was long-term mortality after PCI. Results. Patients were divided into 5 groups according to heart rate quintiles: 1st quintile (heart rate <66 beats/min; n=1123), 2nd quintile (heart rate ≥66 beats/min to 72 beats/min; n=1010), 3rd quintile (heart rate ≥72 beats/min to 78 beats/min; n=1442), 4th quintile (heart rate ≥78 beats/min to 84 beats/min; n=1211), and 5th quintile (heart rate ≥84 beats/min; n=1263). After multivariate Cox regression analyses, the respective risks of ACM, CM, and MACEs were increased 79.1% (hazard risk (HR) = 1.791, 95% CI: 1.207–2.657, P=0.004), 56.9% (HR = 1.569, 95% CI: 1.019–2.416, P=0.041), and 25.5% (HR = 1.255, 95% CI: 0.990–1.590, P=0.060) in the 4th quintile and 98.7% (HR = 1.987, 95% CI: 1.344–2.937, P=0.001), 98.8% (HR = 1.988, 95% CI: 1.310–3.016, P<0.001), and 0.36.1% (HR = 1.361, 95% CI: 1.071–1.730, P=0.012) in the 5th quintile compared with those in the 1st quintile. Patients with a heart rate of ≥80 beats/min had 89.4%, 115.2%, and 39.1% increased risk of ACM, CM, and MACEs, respectively, compared to those patients with a heart rate of <80 beats/min. Conclusion. The present study indicated that the resting heart rate is an independent predictor of adverse long-term outcomes in CAD patients who underwent PCI.